Kontestasi dan Simbolisme Otoritas Tarekat: Analisis Clifford Geertz atas Ideologi JATMAN dan JATMA Aswaja di Indonesia - Fitri, Nasywa Zaakiyatul; Khoiriyah, Nur Alfiyatul; Uyun, Quratul; Irama, Yoga (Postgraduate Studies UIN Sunan Ampel Surabaya, 2025)
This study examines the ideological contestation between two Sufi organizations within Nahdlatul Ulama (NU), namely Jam’iyyah Ahluth Thariqah al-Mu’tabarah an-Nahdliyyah (JATMAN) and Jam’iyyah Ahlith Thariqah al-Mu’tabarah Aswaja (JATMA Aswaja). Both entities share a similar vision of spiritual da‘wah but pursue different paths in constructing religious authority. JATMAN emphasizes the continuity of NU’s traditions and institutional structures, while JATMA Aswaja—led by Habib Luthfi bin Yahya—promotes a more inclusive, progressive, and community-empowering Sufi approach. The purpose of this study is to analyze their ideological narratives, religious symbols, and socio-religious impacts. Employing qualitative library research, this study applies Clifford Geertz’s symbolic theory, which views religion as a system of meaning expressed through symbols and rituals. Data were collected from organizational documents, public sermons, online news, journal articles, and related theses. The findings indicate that the conflict between JATMAN and JATMA Aswaja is not merely structural but also symbolic. Differences in the use of symbols and ritual styles reflect divergent ideologies and da‘wah strategies. This contestation significantly influences the social, educational, economic, and cultural aspects of traditionalist Muslim communities. The study contributes to a deeper understanding of Sufi authority and symbolic construction within the broader context of Indonesia’s moderate Islamic movements.